Representation of Threatened Biodiversity in Protected Areas and Identification of Complementary Areas for Their Conservation: Plethodontid Salamanders in Mexico. (February 2019) - García-Bañuelos, Paulina; Rovito, Sean M.; Pineda, Eduardo
Protected areas (PAs) have been the most important conservation instrument worldwide and are reaching the coverage percentage suggested internationally (17%), but with the risk of not being ecologically representative, which is particularly concerning for threatened species. Using a database of records from museums, literature, and our fieldwork, we evaluated the representation of 132 plethodontid salamander species, a highly threatened group, in the PAs of Mexico. We assessed the importance of PAs, according to the type of governance, to represent the salamander species diversity, estimating the proportion of suitable habitat within PAs where salamanders occur and detecting potential areas to protect threatened species that are outside of PAs. Approximately 40% of plethodontid species, including threatened species, have not been recorded in PAs. A set of federal PAs harbor the greatest number of species, while state, community, and private PAs have different species composition and a high complementariness to federal areas. In 82% of PAs with plethodontid records, suitable habitat covers more than half of their extent. To protect the 36 threatened plethodontid species that have not been recorded in any PA, we detected 26 potential sites, as well as 12 close and suitable established PAs, to complement the protection of threatened species. Different types of governance of PAs are highly complementary to protect threatened species, but not all PAs seem to have the proper conditions for their survival.